Integration of Ethics And Morals In Educational Communication - Abubakar, Abubakar (International Journal on Advanced Science, Education, and Religion, 2024)
This paper discusses the importance of integrating ethics and morals in educational communication to create a harmonious and meaningful learning environment, and support the formation of student character. Ethics that include values ​​such as honesty, responsibility, and openness, and morals that emphasize honesty, patience, and compassion, are the main foundations of interactions in schools. The application of these values ​​not only improves the quality of learning, but also helps shape students who are moral, ethical, and responsible in their social lives. The learning process that focuses on the integration of ethics and morals ensures that education does not only pursue academic achievement, but also supports character development. Communication patterns based on moral principles create a fair, empathetic, and respectful classroom atmosphere, strengthening relationships between teachers, students, and between students. However, modern challenges such as shifting social values ​​and academic pressures can be obstacles to the application of ethics and morals. With the right approach and shared commitment, these obstacles can be overcome, so as to form a generation that is not only academically superior, but also has strong morals and ethics to contribute positively to society.